Development of an amperometric glucose biosensor based on the immobilization of glucose oxidase on the Se-MCM-41 mesoporous composite - Yusan, Sabriye; M. Rahman, Mokhlesur; Mohamad, Nasir A.N.; ,, Tengku M. Arrif; Abdul Latif, Ahmad Zubaidi; Md Aris, Mohd Aznan; Wan Nik, Wan Sani (Hindawi, 2018)
A new bioenzymatic glucose biosensor for selective and sensitive detection of glucose was developed by the immobilization of glucose oxidase (GOD) onto selenium nanoparticle-mesoporous silica composite (MCM-41) matrix and then prepared as a carbon paste electrode (CPE). Cyclic voltammetry was employed to probe the catalytic behavior of the biosensor. A linear calibrationplotisobtainedoverawideconcentrationrangeofglucosefrom1×10−5 to2×10−3M.Underoptimalconditions,the biosensor exhibits high sensitivity (0.34µA·mM−1), low detection limit (1×10−4M), high aﬃnity to glucose (Km0.02mM), and also good reproducibility (R.S.D. 2.8%, n 10) and a stability of about ten days when stored dry at +4°C. Besides, the eﬀectsofpHvalue,scanrate,mediatoreﬀectsontheglucosecurrent,andelectroactiveinterferenceofthebiosensorwerealso discussed. As a result, the biosensor exhibited an excellent electrocatalytic response to glucose as well as unique stability and reproducibility.